Determination of Fatty Acid Composition in Muscle Tissues of Squalius semae Turan, Kottelat & Bayçelebi, 2017 in Kuzgun Dam (Erzurum) - Özçiçek, Esin; Kocabaş, Mehmet; Kutluyer Kocabaş, Filiz; Kirmizikaya Özmen, Görkem; Yilmaz, Ökkeş (Ataturk Universitesi, 2025)
In this study, the fatty acid profile in Squalius semae muscle tissue captured from Kuzgun Dam was determined using gas chromatography. As a result of the study, a total of 26 fatty acids were identified, including 9 saturated fatty acids (SFA), 10 monounsaturated fatty acids (MUFA) and 7 polyunsaturated fatty acids (PUFA). Our results showed that polyunsaturated fatty acids (PUFA) (46.49%) were found in higher proportion than saturated fatty acids (SFA) in muscle tissue, followed by MUFAs (28.01%) and SFAs (25.5%). Palmitic acid (C16:0) (16.19%) is the main saturated fatty acid, while docosahexaenoic acid (DHA, C22:6 n?3) (13.75%) and eicosapentaenoic acid (EPA, C20:5 n?3) (12.18%) was determined as the main polyunsaturated fatty acid. In conclusion, S. semae is nutritionally valuable for human consumption and can be consumed by the consumer as an alternative food source. © 2025, Ataturk Universitesi. All rights reserved.
Kuzgun Barajı’nda (Erzurum) Yaşayan Squalius semae Turan, Kottelat & Bayçelebi, 2017 Türünün Kas Dokularındaki Yağ Asidi Kompozisyonunun Belirlenmesi
Keywords: Fatty acid; Kuzgun Dam; Squalius semae